Comparison of the long‐term impact and clinical outcomes of fewer doses and standard doses of human papillomavirus vaccine in the United States: A database study. Issue 8 (10th February 2020) - Rodriguez, Ana M.; Zeybek, Burak; Vaughn, Micah; Westra, Jordan; Kaul, Sapna; Montealegre, Jane R.; Lin, Yu‐Li; Kuo, Yong‐Fang
Abstract : Background: Human papillomavirus (HPV)–related disease remains a significant source of morbidity and mortality, and this underscores the need to increase HPV vaccination to reduce the burden of the disease. The objective of this study was to examine the association between the number of HPV vaccine doses and the risk of histologically confirmed preinvasive cervical disease and high‐grade cytology. Methods: This retrospective matched cohort study used administrative data from Optum's Clinformatics DataMart Database to identify females aged 9 to 26 years who received 1 or more quadrivalent HPV vaccine doses between January 2006 and June 2015. Cases and controls were matched on region, age, sexually transmitted disease history, and pregnancy. All had a Papanicolaou test ≥1 year after the date of the matched case's final dose. Cox proportional hazards models were used to examine the association between the number of HPV vaccine doses and the incidence of preinvasive cervical disease and high‐grade cytology. The Kaplan‐Meier method was used to estimate the cumulative incidence rate at the 5‐year follow‐up. Results: The study included 133, 082 females (66, 541 vaccinated and 66, 541 unvaccinated) stratified by the number of HPV vaccine doses and the vaccine initiation age. Among those aged 15 to 19 years, the hazard ratio (HR) for high‐grade cytology for the 3‐dose group was 0.84 (95% confidence interval [CI], 0.73‐0.97), whereas the HRs for histologically confirmed preinvasive cervical disease for 1, 2, and 3 doses were 0.64 (95% CI, 0.47‐0.88), 0.72 (95% CI, 0.54‐0.95), and 0.66 (95% CI, 0.55‐0.80), respectively. Conclusions: The receipt of 1, 2, or 3 doses of an HPV vaccine by females aged 15 to 19 years was associated with a lower incidence of preinvasive cervical disease in comparison with unvaccinated females, and this supports the use of any HPV vaccination in reducing the burden of the disease. Abstract : This study examines the association between varying numbers of human papillomavirus vaccine doses and the risk of cervical intraepithelial neoplasia II/III and atypical squamous cells (which cannot exclude a high‐grade squamous intraepithelial lesion)/high‐grade squamous intraepithelial lesions. The receipt of 1, 2, or 3 human papillomavirus vaccine doses between the ages of 15 and 19 years is associated with a lower risk of cervical intraepithelial neoplasia II/III.